2017
DOI: 10.3350/cmh.2016.0067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the early alanine amininotransferase flare during tenofovir monotherapy in treatment-naïve patients with chronic hepatitis B

Abstract: Background/AimsLittle is known about the effect of early flares on response during first-line tenofovir disoproxil fumarate (TDF) treatment for chronic hepatitis B (CHB). The aim of this study was to investigate the incidence and outcome of early alanine aminotransferase (ALT) flare in treatment-naive patients with CHB during long-term TDF monotherapy. MethodsOne hundred eighty-one treatment-naive CHB patients were treated with a 300-mg once-daily dose of TDF for more than 12 weeks. Virological markers of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…During the natural history or treatment of chronic HBV infection, transient elevations in transaminases (flares) are observed in a minority of subjects, even those with advanced cirrhosis, and are rarely associated with hepatic decompensation, except during acute infection or when HBV DNA titres exceed 10 9 copies/mL. [2][3][4][5][6][7][8][9][10][11] In the absence of hepatic decompensation and viral rebound, transaminase flares are considered to be immune-mediated and may reflect clearance of infected hepatocytes from the liver via T-cell mediated cytolytic mechanisms. 12,13 This is consistent with the well-established correlation of transaminase flares in HBV mono-infection with reduction of viraemia and or HBeAg seroconversion in the absence of treatment 2 or during NUC therapy 7,8 or with HBsAg loss 14 and the establishment of partial cure (HBV DNA ≤2000 IU/mL, normal ALT) or functional cure of HBV (HBV DNA TND, HBsAg <LLOQ, normal ALT) during interferon therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the natural history or treatment of chronic HBV infection, transient elevations in transaminases (flares) are observed in a minority of subjects, even those with advanced cirrhosis, and are rarely associated with hepatic decompensation, except during acute infection or when HBV DNA titres exceed 10 9 copies/mL. [2][3][4][5][6][7][8][9][10][11] In the absence of hepatic decompensation and viral rebound, transaminase flares are considered to be immune-mediated and may reflect clearance of infected hepatocytes from the liver via T-cell mediated cytolytic mechanisms. 12,13 This is consistent with the well-established correlation of transaminase flares in HBV mono-infection with reduction of viraemia and or HBeAg seroconversion in the absence of treatment 2 or during NUC therapy 7,8 or with HBsAg loss 14 and the establishment of partial cure (HBV DNA ≤2000 IU/mL, normal ALT) or functional cure of HBV (HBV DNA TND, HBsAg <LLOQ, normal ALT) during interferon therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In the absence of hepatic decompensation and viral rebound, transaminase flares are considered to be immune-mediated and may reflect clearance of infected hepatocytes from the liver via T-cell mediated cytolytic mechanisms. 12,13 This is consistent with the well-established correlation of transaminase flares in HBV mono-infection with reduction of viraemia and or HBeAg seroconversion in the absence of treatment 2 or during NUC therapy 7,8 or with HBsAg loss 14 and the establishment of partial cure (HBV DNA ≤2000 IU/mL, normal ALT) or functional cure of HBV (HBV DNA TND, HBsAg <LLOQ, normal ALT) during interferon therapy. 3,6,9 Nucleic acid polymers (NAPs) selectively block the assembly / secretion of HBV subviral particles (SVP) 15,16 from hepatocytes harbouring cccDNA or integrated HBV DNA, 17 allowing clearance of serum HBsAg by host mediated processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study by Seo et al [ 11 ], 7 of 181 CHB patients (3%) showed early ALT flare (>10×ULN) without viral breakthrough during administration of TDF, and all of them recovered without decompensation and were able to maintain virological response. Although TDF is one of the highly potent NUCs that induce rapid reduction of viral load, a few subjects taking TDF showed early ALT flare without transient decompensation [ 12 , 13 ].…”
mentioning
confidence: 99%
“…In conclusion, Seo et al [ 11 ] showed that early ALT flare on highly potent NUC was relatively safe and led to successful virological responses in compensated CHB patients. In addition, to achieve partial immune reconstitution by NUCs, additional immune therapy is expected to completely eliminate HBV in the liver in further investigations.…”
mentioning
confidence: 99%